1986
DOI: 10.1182/blood.v68.2.372.bloodjournal682372
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR-associated invariant chain is highly expressed in chronic lymphocytic leukemia

et al.

Abstract: Total RNA extracted from peripheral blood lymphocytes of a patient with B-cell chronic lymphocytic leukemia (CLL) and the poly (A+) RNA was purified. A cDNA library was constructed and approximately 4,000 clones were screened in order to identify genes preferentially expressed in CLL. A relatively low repetition frequency characterizes the majority of the abundant mRNA species present in CLL lymphocytes. One clone, corresponding to the mRNA encoding the HLA-DR-associated invariant chain, was selected and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Invariant y-chain mRNA is made in human blood cells and their precursors but has not been detected in a variety of other human tissues (10), such as among various leukemic leukocyte populations the highest levels of y-chain mRNA were found in patients with CLL. These data support a relationship between high levels of y-chain mRNA and the nonproliferating condition of the cell (10,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invariant y-chain mRNA is made in human blood cells and their precursors but has not been detected in a variety of other human tissues (10), such as among various leukemic leukocyte populations the highest levels of y-chain mRNA were found in patients with CLL. These data support a relationship between high levels of y-chain mRNA and the nonproliferating condition of the cell (10,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study to identify the cDNAs that are preferentially expressed in human leukemias, we selected a clone (p7-2D-1) that was more highly expressed in chronic lymphocytic leukemia (CLL) than in several other tissues (9). Subsequent experiments have shown that this gene is expressed in human blood cells and their precursors but not in placenta, liver, kidney, pancreas, gut, or muscle (10). In normal cells the highest expression is found in resting peripheral blood B-lymphocytes. In this communication we present the nucleotide sequence of the structural gene with its 5' and 3' flanking regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anti‐MIF Ig therapy was shown to suppress tumor growth [42]. CD74 overexpression was observed in various cancers [43–48] including CLL [49,50]. CD74 expression in solid tumors has been suggested to serve as a prognostic factor, with higher relative expression of CD74 behaving as a marker of disease progression [51].…”
Section: Mifmentioning
confidence: 99%